Sextíu kíló af kjaftshöggum - Hallgrímur Helgason 1959- (JPV útgáfa, 2021)
This is an independent sequel to Sextíu kíló af sólskini (2018) by Hallgrímur Helgason. The story is still set in the fictitious Icelandic fjord Segulfjörður and the reader swept away on the dance floor at the beginning of a herring fishing adventure that was to reach its pinnacle decades later. Still Hallgrímur Helgason focuses on the fate of the lower and working classes and their continuous struggle.